Grading criteria for disease severity by pemphigus disease area index. Issue 11 (November 2014) - Shimizu, Tomoko; Takebayashi, Toru; Sato, Yuji; Niizeki, Hironori; Aoyama, Yumi; Kitajima, Yasuo; Iwatsuki, Keiji; Hashimoto, Takashi; Yamagami, Jun; Werth, Victoria P.; Amagai, Masayuki; Tanikawa, Akiko
Abstract Pemphigus is a group of autoimmune blistering diseases that affect the skin and mucous membranes. A reliable and accurate disease severity tool to assess pemphigus severity is crucial for managing pemphigus and for clinical trials. The purpose of this study was to compare the pemphigus disease area index activity score (PDAI), the Japanese pemphigus disease severity score (JPDSS) and the physician's subjective impression, and also to find appropriate severity grading cut‐offs for the PDAI. We also evaluated the correlation between PDAI activity score and the JPDSS. Thirty‐seven pemphigus patients and 110 assessments were analyzed in this study. The optimal points of pemphigus disease severity score in PDAI were: mild (0–8), moderate (9–24) and severe (≥25). In mild or moderate cases, the JPDSS was well correlated with the PDAI, but in severe cases the JPDSS reached a plateau at a PDAI score of approximately 30. The PDAI evaluates disease severity more accurately than the JPDSS, particularly in severe cases. The PDAI is not only a useful tool to measure the extent of cutaneous lesions, but also an excellent scoring system for evaluating pemphigus disease severity.